RANCANG BANGUN MODUL E-PORTOFOLIO AGILE UNTUK PENILAIAN CPL - Hariyanto Hariyanto; Marini Marini; Arifin Setiabudi (POLITEKNIK LP3I JAKARTA, 2025)
Digital transformation in the era of Society 5.0 requires polytechnics to integrate information technology into academic management, particularly in the assessment of Graduate Learning Outcomes (CPL). The dominance of manual practices still creates challenges in documentation and transparency, thus an integrated e-portfolio module is needed. This study adopts the Agile framework with iterative stages including needs analysis, system design, module implementation, and testing. Needs analysis was conducted through interviews with lecturers and students to identify obstacles in CPL assessment. The practical use of the e-portfolio module is evident in documenting student achievements such as projects, certification, and academic records that can be accessed by lecturers for assessment. The result show that the system is more responsive, transparent, and supportive of study program accreditation. Furthermore, the Agile-based development model proved adaptive to institutional needs and can be replicated in other polytechnics to strengthen graduate competitveness in the digital era.